Alexander Hamilton - Chernow, Ron. (Penguin Press, 2004)
"Alexander Hamilton was arguably the most important figure in American history who never attained the presidency, but he had a far more lasting impact than many who did." "An illegitimate, largely self-taught orphan from the Caribbean, Hamilton rose with stunning speed to become George Washington's aide-de-camp, a battlefield hero, a member of the Constitutional Convention, the leading author of The Federalist Papers, and head of the Federalist party. As the first treasury secretary, he forged America's tax and budget systems, customs service, coast guard, and central bank. Chernow offers the whole sweep of Hamilton's turbulent life: his exotic, brutal upbringing; his brilliant military, legal, and financial exploits; his titanic feuds with Jefferson, Madison, Adams, and Monroe; his shocking illicit romances; his enlightened abolitionism; and his famous death in a duel with Aaron Burr in July 1804." "Throughout, Chernow blends Hamilton's public and private selves to present a fully rounded portrait of this handsome, witty, controversial genius and his poignant relations with his wife, Eliza, and their eight children. Hamilton's countless exploits never cramped his prolific literary labors. Chernow brings to light nearly fifty previously undiscovered essays as he explores Hamilton's fiery journalism, his youthful poetry, his magisterial state papers, and his revealing missives to colleagues and friends. Moreover, he conjures up portraits of Hamilton's celebrated peers, Washington, Adams, Jefferson, Madison, Monroe, and Burr with all their shortcomings as well as their oft-sung triumphs."--BOOK JACKET.